IMPLEMENTASI MODEL PEMBELAJARAN PROBLEM BASED LEARNING PADA MATA PELAJARAN PKN DI SEKOLAH DASAR (SD) UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA - Mami H. Suki; Dwisye M. B. Poyck; Susanti Wawa (STKIP Subang, 2026)
This study aims to determine the implementation of the Problem Based Learning (PBL) model in Civic subjects at elementary school to improve students’ critical thinking skills. This study used a Quasi-Experimental method with a Nonequivalent Control Group Design involving 12 fifth-grade students from class V A at SDI Perumnas 1, consisting of 6 students in the experimental group and 6 students in the control group. Data were collected through pre-test and post-test of critical thinking skills using essay questions that required students to analyze, evaluate information, provide arguments, and draw conclusions. The results showed that the experimental group had an average gain of 56.6, higher than the control group, which only reached 35. The proportion of students with great improvement in the experimental group reached 40%, greater than the control group (33.3%). The test results showed a significant difference between the learning improvement of the experimental group compared to the control group. The PBL model proved to be effective in improving students’ critical thinking skills through a real problem-based approach that required students to analyze and evaluate based on the FRISCO criteria (Focus, Reason, Inference, Situation).